Investigating a redesigned physics course for future elementary teachers - Fracchiolla, Claudia (Kansas State University, 2016)
There is a growing concern that the number of students graduating with a STEM major in the U.S. is insufficient to fill the growing demand in STEM careers.  In order to fulfill that demand, it is important to increase student retention in STEM majors and also to attract more students to pursue careers in those areas.  Previous research has indicated that children start losing interest in science at the elementary level because science is taught with a focus on learning vocabulary and ideas rather than learning through inquiry-based techniques.  A factor that affects the quality of science education at the elementary level is the preparation of elementary teachers. Many elementary teachers feel unprepared to teach science because they lack adequate content knowledge as well as the pedagogical content knowledge (PCK) for teaching the subject.  Previous studies of teacher preparation in science identified some areas with which pre-service teachers need assistance.  One of these areas is understanding children’s ideas of science. To address that issue, this dissertation investigates whether the use of an instructional approach that teaches physics phenomena along with an understanding of how children think about the physical phenomena promotes changes in students’ knowledge of children’s ideas and use of those ideas in instructional and assessment strategies.  Results indicated that students who were explicitly exposed to knowledge of children’s ideas more often incorporated those ideas into their own microteaching and demonstrated higher levels of sophistication of knowledge of children’s ideas, instructional strategies, and assessment strategies that incorporated those ideas.  This research explores an instructional model for blending physics content and pedagogical content knowledge.
Keywords: Children's ideas about science; Future elementary teachersPedagogical content knowledge